48 EXPLORING RESIDENTS' PERCEPTIONS OF SOCIAL AND LEISURE OCCUPATIONAL CHOICE WITHIN NATIONAL NURSING HOME CARE FACILITIES. (25th October 2022) - Ryan, C; Keane, J; Usher, R
Abstract: Background: National standards state that nursing homes in Ireland must provide residents with a variety of engaging activities that accommodate their needs and preferences. Despite this, residents are at risk of experiencing occupational deprivation as a result of limited choices within these settings. Due to the subjective nature of occupational choice, the objective of this study is to analyse residents' perceptions of leisure and social occupational choice in nursing homes in Ireland. Methods: The study adopted a qualitative-descriptive design. Six residents from three different nursing homes participated in two semi-structured interviews that analysed their leisure and social occupational engagement within their nursing home. Results: The data identified two main themes that were divided into six related sub-themes. Residents' felt their social and leisure occupational choice was influenced by: (1) environmental factors (the cultural, social, physical, and temporal contexts of the nursing home) and (2) personal attributes (residents' health status and personal attitudes). Conclusion: Residents' leisure and social occupational choices are substantially influenced by the cultural context of the nursing home. This stresses the significant need for person-centred care in nursing homes, in order to promote occupational choice. The findings also highlight the benefits of accessible communal spaces to enable unstructured social interaction. Occupational therapists are essential to support the leisure and social occupational choices of nursing home residents and minimise occupational deprivation, by building residents' skills, providing staff education and modifying tasks and/or the environment.